2020
DOI: 10.1186/s12891-020-3105-z
|View full text |Cite
|
Sign up to set email alerts
|

Sacroiliac joint variation associated with diffuse idiopathic skeletal hyperostosis

Abstract: Background: Diffuse idiopathic skeletal hyperostosis (DISH) is characterized by the ossification of vertebral bodies and peripheral entheses. However, variations in sacroiliac (SI) joint change in patients with DISH have not been fully clarified. The purpose of this study was to evaluate SI joint variation in patients with DISH in comparison with a non-DISH population. Methods: A total of 342 SI joints in 171 patients (DISH+, n = 86; DISH-, n = 85) who had undergone lumbar spine surgery were analyzed by comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
1
14
0
3
Order By: Relevance
“…Consequently, exclusion of lesions from the ventral third of the joint increased diagnostic performance. Ankylosis is widely regarded as the most specific imaging marker of axSpA and our findings support this claim; however, alternative explanations for ankylosis exist and should be considered during image interpretation (ie, sequelae of septic arthritis, which generally affect only one joint, or diffuse idiopathic skeletal hyperostosis,16 which presents with extensive capsular ossification which may be confused with true ankylosis) 17…”
Section: Discussionsupporting
confidence: 81%
“…Consequently, exclusion of lesions from the ventral third of the joint increased diagnostic performance. Ankylosis is widely regarded as the most specific imaging marker of axSpA and our findings support this claim; however, alternative explanations for ankylosis exist and should be considered during image interpretation (ie, sequelae of septic arthritis, which generally affect only one joint, or diffuse idiopathic skeletal hyperostosis,16 which presents with extensive capsular ossification which may be confused with true ankylosis) 17…”
Section: Discussionsupporting
confidence: 81%
“…Conversely, in the SIJ of patients with DISH, only ligamentous area obliteration and mild synovial area narrowing can occur; however, SIJ fusion is not observed 1 . However, some other studies have reported that 23% of DISH is associated with fusion 15,19 , even though the DISH diagnosis does not require this involvement based on the Resnick criteria 8 . A previous study suggested that SIJ fusion occurring both in patients with DISH and AS may be possibly due to similar developmental pathways, leading to in ammation-associated enthesitis in younger patients in AS and more mechanistically associated enthesopathy in older patients with DISH 19 .…”
Section: Discussionmentioning
confidence: 99%
“…DISH was diagnosed with anterior longitudinal ligament ossi cation in at least four contiguous vertebral bodies as previously reported 17,18 . Previous reports 15,19,20 demonstrated that pelvic ndings were excluded from the diagnostic criteria. Patients with AS were retrospectively enrolled in three institutions.…”
Section: Study Design and Populationmentioning
confidence: 99%
“…La hiperostosis esquelética idiopática difusa (DISH) es un trastorno caracterizado por osificación y calcificación a lo largo de la cara anterolateral de los cuerpos vertebrales y entesis periféricas (6).…”
Section: Discussionunclassified
“…En ocasiones se dificulta el diagnóstico diferencial, porque pueden existir ambas patologías. También se pueden observar hiperostosis en el tobillo, en la cara posterior del calcáneo y en el codo, en la inserción del tríceps en el olécranon (2,6).…”
Section: Discussionunclassified